Type IV Pili-Independent Photocurrent Production by the Cyanobacterium Synechocystis sp. PCC 6803 - Thirumurthy, Miyuki A.; Hitchcock, Andrew; Cereda, Angelo; Liu, Jiawei; Chavez, Marko S.; Doss, Bryant L.; Ros, Robert; El-Naggar, Mohamed Y.; Heap, John T.; Bibby, Thomas S.; Jones, Anne K. (Frontiers in Microbiology, 2020)
Biophotovoltaic devices utilize photosynthetic organisms such as the model cyanobacterium Synechocystis sp. PCC 6803 (Synechocystis) to generate current for power or hydrogen production from light. These devices have been improved by both architecture engineering and genetic engineering of the phototrophic organism. However, genetic approaches are limited by lack of understanding of cellular mechanisms of electron transfer from internal metabolism to the cell exterior. Type IV pili have been implicated in extracellular electron transport (EET) in some species of heterotrophic bacteria. Furthermore, conductive cell surface filaments have been reported for cyanobacteria, including Synechocystis. However, it remains unclear whether these filaments are type IV pili and whether they are involved in EET. Herein, a mediatorless electrochemical setup is used to compare the electrogenic output of wild-type Synechocystis to that of a pilD deletion mutant that cannot produce type IV pili. No differences in photocurrent, i.e. current in response to illumination, are detectable. Furthermore, measurements of individual pili using conductive atomic force microscopy show these structures are not conductive. These results suggest that pili are not required for EET by Synechocystis, supporting a role for shuttling of electrons via soluble redox mediators or direct interactions between the cell surface and extracellular substrates.